2021
DOI: 10.1039/d0dt01367f
|View full text |Cite
|
Sign up to set email alerts
|

P-Alkynyl functionalized benzazaphospholes as transmetalating agents

Abstract: Exposure of 10π-electron benzazaphosphole 1 to HCl, followed by nucleophilic substitution with the Grignard reagent BrMgCCPh afforded alkynyl functionalized 3 featuring an exocyclic –CC–Ph group with an elongated P–C bond (1.7932(19) Å).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The X-ray crystallographic analysis also shows that the N-atom of related P-halogenated benzazaphospholes 1–F through 1–I is planar (sp 2 ); therefore, their exocyclic P–X bonds are also susceptible to N LP → σ*(P–X) negative hyperconjugation. Previously, a DFT/NBO comparison of 1– and 3–Cl with their corresponding P–CCPh derivatives indicated that the shorter P–X (X = Cl, CCPh) bonds observed in functionalized benzazaphospholes were a result of less-extensive N-lone pair delocalization into the P–X σ* orbitals than the NHP analogues (one vs two nitrogen donors) . With the halogen series of P-heterocycles 1 and 3 completed, additional comparisons can be made, as presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The X-ray crystallographic analysis also shows that the N-atom of related P-halogenated benzazaphospholes 1–F through 1–I is planar (sp 2 ); therefore, their exocyclic P–X bonds are also susceptible to N LP → σ*(P–X) negative hyperconjugation. Previously, a DFT/NBO comparison of 1– and 3–Cl with their corresponding P–CCPh derivatives indicated that the shorter P–X (X = Cl, CCPh) bonds observed in functionalized benzazaphospholes were a result of less-extensive N-lone pair delocalization into the P–X σ* orbitals than the NHP analogues (one vs two nitrogen donors) . With the halogen series of P-heterocycles 1 and 3 completed, additional comparisons can be made, as presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis and Structures of Dearomatized and P-Halogenated Benzazaphospholes (1). Dearomatization of the five-membered ring of N-Dipp (Dipp = 2,6-diisopropyl-phenyl)-substituted benzazaphosphole 22 2 with HCl afforded 1−Cl, 18 which has been previously characterized by NMR spectroscopy, elemental analysis, and X-ray crystallography. Given that 1−Cl served as an excellent precursor to iodo analogue 1−I via its treatment with trimethylsilane (TMS)− I, 23 we hypothesized that related substitution reactions would generate 1−F and 1−Br, respectively (Scheme 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations